2018
DOI: 10.3892/mco.2018.1569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes and complications between the Harmonic FOCUS and conventional surgery for open thyroidectomy

Abstract: Abstract. The aim of the present study was to evaluate the potential advantages of the ultrasonic scalpel compared with the conventional technique in thyroid surgery. Patients with resectable thyroid cancer and Basedow's disease were assigned to ultrasonic scalpel or conventional technique (knot-tying and electrocoagulation). The present study used the Harmonic FOCUS ® (HF) as an ultrasonic scalpel. Between February 2013 and May 2016, 45 patients were enrolled into the study. Duration of the surgery was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…However, the difference in the post-operative length of stay was less than 1 day. Furthermore, whereas the post-operative length of stay in the present study is comparable with that of previous studies reported from Japan (37,38,39), it is considerably longer than that of previous studies from other countries. This is presumably because the length of stay in Japan is generally long, being approximately three times that in Western countries (40), this difference reportedly being attributable to differences in health care systems (41).…”
Section: E210081 T Konishi Et Alsupporting
confidence: 86%
“…However, the difference in the post-operative length of stay was less than 1 day. Furthermore, whereas the post-operative length of stay in the present study is comparable with that of previous studies reported from Japan (37,38,39), it is considerably longer than that of previous studies from other countries. This is presumably because the length of stay in Japan is generally long, being approximately three times that in Western countries (40), this difference reportedly being attributable to differences in health care systems (41).…”
Section: E210081 T Konishi Et Alsupporting
confidence: 86%
“…As regards operative times, shorter operations obtained using the energy-based devices rather than the traditional technique, as widely described in the literature [ 14 , 15 , 16 , 18 , 19 , 21 , 23 ], make it possible to increase the number of operations in the same surgical session, thus optimizing the utilization of the operating theatres and reducing the waiting lists. Furthermore, shorter operative times reduce anaesthesia times, allowing for faster recoveries after surgery, and decrease anaesthesia costs of each individual procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several reports comparing the energy-based devices with the traditional technique exist. In most of these studies, Harmonic Focus and LigaSure Small Jaw (a device that works by means of advanced bipolar energy) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were evaluated. Far fewer studies that compare the different devices with each other exist [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies found no difference in complication rates when comparing EBDs vs. conventional clamp and tie techniques [33,35], others highlighted a reduction in postoperative transient hypocalcemia, postoperative cervical hematoma, and definitive recurrent laryngeal nerve palsies compared to standard hemostasis [36,37]. Similar results regarding postoperative hemorrhage were found comparing LS vs. the conventional clamp and tie technique, as highlighted by Grøndal et al [38], while other authors did not find any difference regarding postoperative cervical hematoma or RLN injury rates when EBD was compared to the standard technique [11,39,40].…”
Section: Improve Oncological Radicalitymentioning
confidence: 99%
“…The use of HF is extensively studied in the literature, and all studies agree that it significantly reduces operative times compared to standard clamp and tie techniques [32][33][34][35][36].…”
Section: Improve Oncological Radicalitymentioning
confidence: 99%